ANALISIS KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN TEMATIK PADA SISWA MADRASAH IBTIDAIYAH MUHAMMADIYAH - Ulfha, Nur; Kusuma, Yanti Yandri; Sumianto, Sumianto; Sutiyan, Ory Syafari Jamel (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This study aims to analyze critical thinking skills in thematic learning in fourth grade students of MIM Simpang Kubu, Kampar District. The research method used is descriptive qualitative research. The subjects of this study were 16 grade IV students and 1 grade IV MIM Simpang Kubu teacher, Kampar District. Data collection is done by using Questionnaire, Interview, Observation. Critical Thinking Skills in Thematic Learning based on all indicators with an average percentage of 78.75% is in the very high category. Validation of research data using triangulation techniques, time and source triangulation. The results showed that the average percentage of the highest indicator was to provide a simple explanation in the Very critical category and the lowest indicator was to build basic skills in the critical category. Most students are still not able to ask questions, responses and comments during learning. Based on the research, the teacher in explaining the lesson is expected to be active and interactive in teaching so that students can be interested and pay attention to the ongoing learning discussion